2013
DOI: 10.1002/phy2.101
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for glucocorticoid-mediated hypertension after uninephrectomy

Abstract: Recently, evidence was presented that uninephrectomy induces salt-sensitive hypertension in rats. The increase in blood pressure was abrogated by a mineralocorticoid receptor antagonist but not by an aldosterone synthase inhibitor. Here, we hypothesize that mineralocorticoid receptor activation occurred by an 11beta-hydroxy-glucocorticosteroid, as a consequence of dysregulated 11beta-hydroxysteroid dehydrogenase enzymes. Therefore, 3-week-old Sprague-Dawley rats were either uninephrectomized or sham operated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Although, uninephrectomy alone might have caused a mild increase in blood pressure and markers of oxidative stress when compared with the 8% salt and uninephrectomy untreated group, which must have exacerbated the effects in the untreated group. This assertion corroborates an earlier finding that uninephrectomy might give protection against an increase in blood pressure [1]. A previous study linked the blood pressure increases the effect of uninephrectomy to its interference with L-arginine metabolism [17].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although, uninephrectomy alone might have caused a mild increase in blood pressure and markers of oxidative stress when compared with the 8% salt and uninephrectomy untreated group, which must have exacerbated the effects in the untreated group. This assertion corroborates an earlier finding that uninephrectomy might give protection against an increase in blood pressure [1]. A previous study linked the blood pressure increases the effect of uninephrectomy to its interference with L-arginine metabolism [17].…”
Section: Discussionsupporting
confidence: 91%
“…The kidneys are very important organs that are involved in the maintenance of arterial blood pressure and modulation of hypertension. While uninephrectomy has been said to have less impact on human well-being, however, studies have also shown that it protects a subsequent increase in blood pressure [1]. However, a compensatory mechanism is developed in uninephrectomized animals which allow the animal to maintain normal blood pressure, in complicated events such as in high salt diet, a uninephrectomized animal develops high blood pressure in addition to increased diuresis [2].…”
Section: Introductionmentioning
confidence: 99%
“…This was not a focus of our study and a systematic analysis of the relationship between dietary salt and HPA activity is currently lacking. Nevertheless, this positive relationship is exaggerated in both clinical and experimental models of salt-sensitive hypertension ( Liu et al, 2008 ; Usukura et al, 2009 ; Bailey et al, 2011 ; Craigie et al, 2012 ; Huesler et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Down regulation of 11 β-HSD2 was also linked with salt sensitive hypertension in human linkage studies and animal models [ 39 , 44 , 45 ]. Unilateral nephrectomy, in animal models, reduced 11 β-HSD2 expression within the remaining kidney and predisposed animals to a salt responsive hypertension [ 39 , 46 , 47 ]. In humans, a number of studies demonstrated a prolonged plasma half-life for cortisol in patients with CKD.…”
Section: Aldosterone Acts On Multiple Tissues and May Act Via Multipl...mentioning
confidence: 99%